Outcome and prognostic factors of desmoplastic medulloblastoma treated within a multidisciplinary treatment concept - Rieken, Stefan; Gaiser, Timo; Mohr, Angela; Welzel, Thomas; Witt, Olaf; Kulozik, Andreas; Wick, Wolfgang; Debus, Jürgen; Combs, Stephanie (BMC cancer, 2010)
Desmoplasia in medulloblastoma is often diagnosed in adult patients and was repeatedly associated with improved results. Today, all medulloblastoma patients receive intensive multimodal treatment including surgery, radiotherapy and chemotherapy. This study was set up to investigate treatment outcome and prognostic factors after radiation therapy in patients with desmoplastic medulloblastomas.
Gesehen am 19.05.2023